Economic Viability of Installations of Photovoltaic Microgeneration in Residencies of a Smart City - Abrao, R. R. [UNESP]; Paschoareli Jr, D. [UNESP]; Silva, A. A.; Lourenco, M.; IEEE (Ieee, 2017)
Smart grids make possible the insertion of distributed generation more securely due to control strategies and access to remote and almost on-line information. Also, it allows a higher interaction of consumers and network and the use of time-based tariffs, which encourage responsible demand. This work presents an economic viability analysis for residential consumers who opt for the installation of photovoltaic microgeneration, comparing conventional tariff and time of use tariff, considering the regulatory models adopted in Brazil.
Keywords: Smart grid; photovoltaic microgerenation; economic viability